Correction to: ‘How the pandemic affected psychological research’ - Gollwitzer, Mario; Nuding, Stephan; Schramm, Leonhard; Glöckner, Andreas; Gruber, Robert; Hajek, Katharina V.; Häusser, Jan A.; Imhoff, Roland; Rudert, Selma C. (Royal Society open science, 2024)
[This corrects the article DOI: 10.1098/rsos.241311.].